The Impacts of Audit Committee Characteristics on Earnings Quality - Ren, Ruonan (2022)
In recent years, frequent corporate earnings management and financial fraud have raised public suspicion about financial figures, especially reported earnings. Audit committees, as one of the important internal mechanisms of corporate governance, have attracted much scholars' attention to their role in earnings quality. The study aims to investigate how relevant audit committee characteristics affect earnings quality. The three audit committee characteristics selected are financial expertise, size and shareholding. Earnings quality is captured via earnings smoothness. Since few scholars in this research field have used UK evidence, the 91 listed firms included in the UK FTSE 100 during 2016-2021 are employed as samples in the paper. By using panel data regression analysis, the financial expertise, size and shareholding of audit committees have no significant effect on the quality of earnings. Despite these effects being insignificant, the empirical evidence in the study still shows that these three selected audit committee characteristics are still weakly and positively associated with earnings quality. It may be suggested that audit committee characteristics could affect earnings quality. These results contribute to the UK previous studies. It is the first study in the UK literature to use earnings smoothness to quantify earnings quality and investigate how it relates to the internal corporate governance mechanisms. Also, it is the first study in the UK literature to supply a finding of relevant audit committee characteristics have no significant influence on earnings smoothness. Besides, the results in the paper could also imply the regulators or policymakers to revise the UK governance code to tighten the role of audit committees.